EFFECTIVENESS OF LEARNING MODEL QUANTUM LEARNING AGAINST STUDENTS’ MMATHEMATICAL CRITICAL THINKING SKILLS - nasution, siti khadijah; Narpila, Suci Dahlya (Prima: Jurnal Pendidikan Matematika, 2025)
Students must have critical thinking skills to face the challenges of complex mathematics learning. Howver, the fact in the field shows that study are still classified as lacking in critical thinking. The purpose of this study was to determine how effective the quantum learning model is on students' mathematical critical thinking skills in the material of arithmetic sequences. This study was conducted at Karya Utama Junior High School in Serdang Bedagai Regency. A quantitative approach was used and a quasi-experimental design using a pretest-posttest control group. The results of the study were conducted randomly, with 30 studies each in the experimental group of class VIII d and the control group of class VIII B. The results showed an average posttest score of the experimental class of 79.66, which was higher than the control class of 70.66, and a significance value of 0.003 <0.05. Therefor, H0 was rejected and ha was accepted. The results showed that the quantum learning model was effective in improving the ability to think critically mathematically.